Molecular epidemiologic analysis of mycobacterium tuberculosis among prison inmates in selected prisons in the Philippines - Montoya, Jaime C.; Borja, Maridel P.; Ang, Concepcion F.; Malabad, John Carlo M.; Yoshiro Murase (Philippine Journal of Science)
"Tuberculosis (TB) remains an important public health problem in developing countries like the Philippines. The success of the National TB Control Program depends on a clear understanding of the dynamics of transmission and spread of TB in high-risk populations in the community. We conducted a molecular epidemiologic analysis of M. tuberculosis isolates collected from inmates with pulmonary TB in selected prisons in the Philippines"-title page.